PERENCANAAN BUS BANDARA PADA BANDAR UDARA DHOHO KEDIRI JAWA TIMUR - Salman Rasendriya; Nugroho Utomo; Fithri Estikhamah (LPPM Universitas Abdurrab, 2026)
Dhoho Airport in Kediri serves as a vital air transportation infrastructure supporting regional mobility. However, no intermodal transport service currently connects Tamanan Terminal to the airport. This study aims to design an airport shuttle bus system that provides an effective and efficient linkage. Data were collected through interviews and questionnaires using the stated preference method, focusing on service effectiveness attributes. The planning analysis refers to the Technical Guidelines of the Directorate General of Land Transportation No. SK.687/AJ.206/DRJD/2002. The proposed mode of transport is the E-Inobus electric bus with a capacity of 24 passengers. The analysis results indicate 15 designated stops along the route, with a total circulation time of 73 minutes. The load factor is estimated at 25%, with an average headway of 13 minutes. A total of bus 20 unitsare required, operating at a frequency of 2 vehicles per hour. The average passenger waiting time is 13 minutes, and the operating speed is set at 30 km/h. This planning is expected to provide an integrated intermodal transport service that enhances accessibility and travel efficiency to and from Dhoho Airport.